Diversity of gut microbes in freshwater and brackish water ricefish (Oryzias minutillus and O. javanicus) from Southern Thailand - Arin Ngamniyom,; Thayat Sriyapai,; Pichapak Sriyapai,; Busaba Panyarachun, (Agriculture and Natural Resources, 2021)
Fish belonging to the genus Oryzias, commonly known as medaka or ricefish, are frequently used as a vertebrate model, especially the Japanese ricefish O. latipes. In Thailand, Thai ricefish (O. minutillus) are widely distributed throughout natural freshwater, whereas Javanese ricefish (O. javanicus) mainly inhabit brackish water along the coast of southern Thailand. To date, nothing has been published on the endosymbionts of Oryzias inhabiting different natural environments in Thailand. The current study used 16S rDNA sequencing to investigate communities of bacteria and photosynthetic unicellular organisms in the gastrointestinal tracts of Thai ricefish from fresh water and in Javanese ricefish from brackish mangrove swamps. The family Aeromonadaceae was identified as the most dominant phylum of the Proteobacteria in Thai ricefish, but not in Javanese ricefish. The cyanobacterium Synechococcus was more prevalent in the gut of Thai ricefish than Javanese ricefish. Among the family Vibrionaceae, the genus Vibrio was found only in Javanese ricefish. In contrast, the genus Escherichia was the predominant class of Gammaproteobacteria in all gut samples of both ricefish species. This study showed that gut microbiomes of Thai and Javanese ricefish each consists of a core group of bacteria and photosynthetic unicellular organisms. Furthermore, microbiota may be dependent on the ricefish species and the different levels of salinity in their environments.